ANALISIS ALIRAN MASSA UAP PADA KATUP KONTROL UREA (UREA GLOBE CONTROL VALVE) DI UNIT PRODUKSI UREA PABRIK 1B PT PETROKIMIA GRESIK - Bandung Arry Sanjoyo; Erwan Adi Saputro; Auliya Ichda; Gelar Panji Gemilar (ROTOR, 2022)
In a process, industrial plants have several tools that require steam to help run the processing of a material. For the heating process, PT. Petrokimia Gresik requires steam. Sometime the steam leak during the process, so it reduces the productivity of this industry. For that reason, the purpose of this calculation is to find out the steam loss during the process, especially in urea globe control valve (PV-723, PV-726, PV-735). The result show that the upstream pressure and temperature at PV-723 are 21 kg/cm2G and 307 oC, upstream pressure and temperature in PV-726 are 5 kg / cm2G and 158 oC, upstream pressure and temperature on PV-735 of 2.5 kg / cm2G and 138 oC. For downstream pressure on all valves is 1.03323 kg/cm2G. The obtained mass flow (F) in each valve is 0.514 tons / hr, 0.86 tons / hr and 1,902 tons / hr. The value of the input mass balance of steam in the system is 82.70 tons/hour and the overall output is74.11 tons/hour. Therefore, the total steam loss in PV-723, PV-726, and PV-735 is around 8.59 tons/hour which mean there are some leak during the process that need to do further investigation.